Monitoring capabilities of busy and overlap directors: Evidence from Australia - Fernández Méndez, C.; Pathan, Md Shams Tabrize; Arrondo García, R. (ELSEVIER SCIENCE BV, 2015)
© 2015 Elsevier B.V. We analyze the effects of multiple board directorships (busy directors) and multiple committee memberships of a board (overlap directors) on four board supervisory outcomes: CEO remuneration, external auditor opinion, audit fees and CEO turnover. Using a panel of 684 Australian listed firms from 2001 to 2011, we find that firms with busy directors pay high remunerations to their CEOs, and experience low CEO pay-performance and low CEO turnover-performance sensitivities. Our results also suggest that firms with overlap directors have a lower probability of receiving a qualified audit opinion and are able to negotiate lower payments, both to their CEOs and to the external auditors. These results hold for alternative specifications and proxies. Our results suggest that busy (overlap) directors are detrimental (beneficial) to the monitoring capability of the board and its committees. Finally, our findings suggest that the negative monitoring effect of busy directors are predominantly observed in large firms where over-commitment problems are severe, while the positive monitoring effects of overlap directors are observed in small firms where directorial positions are less time demanding.